Product Market Competition terhadap Audit Fee dengan Auditor Industry Specialization sebagai Pemoderasi - Nisrina, Naila (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This research aims to examine the influence of product market competition on audit fees and the role of auditor industry specialization as a moderating variable. Using probability sampling method, 1,018 non-financial companies listed on Indonesia Stock Exchange from 2014 to 2018 were selected as research samples. Multiple linear regression was used to analyzed the data. The results showed that product market competition has a negative significant effect on audit fees, while auditor industry specialization has a positive significance or weakens the relationship between product market competition and audit fees. In other words, auditor industry specialization stimulates the increase audit fees even in a competitive market.